Effect of soil buried to mechanical properties of Kenaf fibre reinforced thermoplastic polyurethane composites: article / Muhammad Fahmi Aizat Razali and Noor Fitrah Abu Bakar - Razali, Muhammad Fahmi Aizat; Abu Bakar, Noor Fitrah (2017)
The aim of this research is to study the effect of soil buried to compressive strength properties of Kenaf fiber reinforced thermoplastic polyurethane (KFTPU) composite. Pulverized kenaf core particles was sieved into 3 sizes namely <123µm, 125-300µm and >300µm. Pulverized kenaf core particles reinforced TPU composite was prepared with 3 different percent of kenaf loading of 5wt%, 10wt% and 15wt%. The compressive strength of the composite was tested by using Compressive test machine. The samples were test to see which one have the highest compressive strength and low density. The results of compressive strength at 60% deformation show that sample 125-300µm and 10wt% kenaf loading have the best strength and low density. Thus, the composite with pulverized kenaf core particles size 125300µm and 10wt% kenaf loading was buried into the soil. The buried sample was divided into two categories which at the presence of water and petrol oil. The compressive strength was determined after 1, 2, and 3 weeks. The weight gains by the samples after soil buried were recorded every on 1 week. The compressive strength of the buried composite during the presence of water increased from 2722.75 kPa to 4269.33 kPa for week 1 and week 3 respectively. While the compressive strength of the buried composite during the presence of petrol oil decreased from 3287.47 kPa to 1964.9 kPa for week 1 and week 3 respectively.